Authoritarian resilience through top-down transformation: making sense of Myanmar's incomplete transition. (16th May 2019) - Ruzza, Stefano; Gabusi, Giuseppe; Pellegrino, Davide
Abstract: Starting from the imperfect nature of Myanmar's democracy, this paper aims to answer two questions. First, can Myanmar's transition be defined as a case of democratization, or is it, rather, a case of authoritarian resilience? To state this differently: is the progress enjoyed by Myanmar's polity the outcome of an ongoing process that is supposed to lead to a fully fledged democracy, or, rather, an attempt to enshrine elements of authoritarian governance under a democratic guise? Second, if the balance leans towards the latter instead of the former, how did authoritarian resilience work in Myanmar? The transition is analysed from a long-term perspective, moving from the 1988 pro-democracy uprising up to the most recent events. Data were collected from available published sources and from three fieldworks conducted by the authors in Myanmar. The paper concludes that Myanmar's transition is better understood as a case of authoritarian resilience than as democratization and highlights three core traits of Myanmar's authoritarian resilience: first, the very top-down nature of the political transformation; second, the incumbents' ability to set the pace of political reform through the use of repression and political engineering; and third, the divide-and-rule strategy used as a means to keep contestations separated and local.